2016
DOI: 10.1371/journal.pone.0166260
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Synonymous Codon Usage Bias of Zika Virus and Its Adaption to the Hosts

Abstract: Zika virus (ZIKV) is a mosquito-borne virus (arbovirus) in the family Flaviviridae, and the symptoms caused by ZIKV infection in humans include rash, fever, arthralgia, myalgia, asthenia and conjunctivitis. Codon usage bias analysis can reveal much about the molecular evolution and host adaption of ZIKV. To gain insight into the evolutionary characteristics of ZIKV, we performed a comprehensive analysis on the codon usage pattern in 46 ZIKV strains by calculating the effective number of codons (ENc), codon ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 59 publications
9
58
0
Order By: Relevance
“…Studies have shown that the higher the gene expression level is, the stronger is the preferred use of codon [1][2][3]6,15,16,49,[55][56][57][58][59][60]. In our study, the codon usage bias results of all cotton species were shown in S1 Table. The correlation between the parameters of 4 cotton species and 4 subgenomes had the same rule, except the correlation between G3s and C3s.…”
Section: Correlation Analysis Between Codon Usage Bias Indicesmentioning
confidence: 74%
See 1 more Smart Citation
“…Studies have shown that the higher the gene expression level is, the stronger is the preferred use of codon [1][2][3]6,15,16,49,[55][56][57][58][59][60]. In our study, the codon usage bias results of all cotton species were shown in S1 Table. The correlation between the parameters of 4 cotton species and 4 subgenomes had the same rule, except the correlation between G3s and C3s.…”
Section: Correlation Analysis Between Codon Usage Bias Indicesmentioning
confidence: 74%
“…GC12 represents the average GC content of the first and second positions of the codons. A significant correlation between GC12 and GC3 values means that mutational stress is superior to translation selection in the formation of codon usage bias while non-significant correlation between them reveal that translation selection plays dominant role in codon usage preference [55,[61][62][63]. In our study, firstly we took the nuclear genome CDSs of each cotton species and subgenome as a whole and calculated one GC12/GC3 value per cotton species to analyze the correlation coefficients between GC12 and GC3 in 4 cotton species and 4 subgenomes.…”
Section: Enc (Av)mentioning
confidence: 99%
“…Studies of relative synonymous codon usage (RSCU) bias between viruses and their hosts suggested that viruses tends to evolve codon usage bias that is comparable to their hosts. 10,11 Results from our analysis suggest that 2019-nCoV has most similar genetic information with bat coronovirus and has most similar codon usage bias with snake. More interestingly, an origin-unknown homologous recombination may occured within the spike glycoprotein of the 2019-nCoV, 5 which may explain its cross-species transmission, and limited person-person spread.…”
Section: Introductionmentioning
confidence: 84%
“…It contains a positive‐strand, RNA genome that encodes a single long open reading frame that is posttranslationally modified to generate structural and nonstructural ZIKV proteins . ZIKV can and has evolved rapidly, with distinct strains isolated from numerous locations throughout the world (Refs ; see also Box ). Structural studies of ZIKV indicate that its protein coat, comprised primarily of envelope (E) protein, is similar to other flaviviruses .…”
Section: Zikv Overviewmentioning
confidence: 99%